ChemInform Abstract: Organocatalytic Cascade Reaction for the Asymmetric Synthesis of Novel Chroman‐Fused Spirooxindoles That Potently Inhibit Cancer Cell Proliferation. Issue 50 (December 2015) - Zhou, Rui; Wu, Qinjie; Guo, Mingrui; Huang, Wei; He, Xianghong; Yang, Lei; Peng, Fu; He, Gu; Han, Bo
Abstract: The tandem oxa—Michael—Michael reaction of 2‐nitrovinyl phenols (I) with enal (II) followed by reaction of intermediate chromanes with oxindoles (III) leads to chroman‐fused spirooxindoles (IV) with high enantioselectivities and good diastereoselectivities.